WHY ARE FARMERS WILLING TO JOIN PARTNERSHIPS IN ORGANIC RICE? CASE IN NGAWI ORGANIC CENTER COMMUNITY, EAST JAVA - Tiffany Rahma Abdillah; Netti Tinaprilla; Andriyono Kilat Adhi (Socio-Economics/Agribusiness Department, 2022)
Organic farming is more profitable because of the increasing demand and high product prices. However, it is not easy for farmers to decide on rice farming organically. Farmers faced obstacles such as limited capital, lack of knowledge about organic technology, and no price guarantee for organic farmers who have not been certified organic. It is necessary to develop some policies such as institutions. A partnership is one of the institution's solutions for farmers to increase their willingness to join organic rice farming. This research was conducted in Ngawi Regency, East Java, from March 2020. Ngawi Organic Center Community (KNOC) is a partner institution with experience in pioneering and fostering organic farmers. The research aims to analyze (1) the factors that influence organic rice farmers for decision-making partnership; (2, the mechanism of organic rice partnership; and (3) the benefits farmers get from the partnership. Logistic Regression used to analyze the factors that influence the farmers' decisions. Descriptive analysis is used to investigate the mechanism of organic rice partnership between organic rice farmers and KNOC. The descriptive analysis also describes the benefits of partnerships received by farmers. The study results show that farming experience, land area and frequency of extension significantly affect farmers' decision making. The organic rice partnership mechanism regulated in a written contract, with the Agribusiness Operational Cooperation partnership pattern. The high price of organic rice is the most profitable partnership benefit for farmers (81,67%).